في تنمية مهارة التعبير الكتابي لدى طالبات قسم الإعداد اللغوي بجامعة الراية (STAD) فاعلية طريقة التحصيل الدراسي - Neng Silvia (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
Student Team Achievement Division (STAD) techniques is a cooperative learning strategy in which learners work in heterogenous groups to achieve a common goal. This research aimed to identity the effectivieness Student Team Achievement Division (STAD) techniques in developing the skill of written expression and to identity the importance of the skill of written expression for female student. The study implemented quantitative approach or experimental approach. The researcher prepared a questionnaire skill of written expression. Then the researcher applied the pre-test and post-test to the subject of this research, and they were thirty students from the different academic achievement. The sample was distributed into two groups, fifteen students were in the experimental group while fifteen students were in the control group. The study found the result: The first result was the targets of the skill of written expression are ten importance targets. And the second one showed the difference result between the scores of experimental group when used the STAD cooperating learning and the scores of control group who studied by the traditional teaching method. The effects showed that the scores of experimental groups was better than the other.